SED-Kontakte der katholischen Kirche im Bistum Dresden-Meißen - Haese, Ute (Kirchliche Zeitgeschichte, 1995)
This article takes up once again the discussion about the Catholic Church's contasts with the Ministry of State Security in the former East Germany, seeking to put these in a wider context, and discussing the role and function of non-Catholic scholars in their "assessments" of the State's controls in general. In the second half, the internal church as well as the social conditions and factors are described which made it possible (or caused) Bishop Schaffran of Dresden-Meißen in the 1980s to take up official contacts with the ruling SED Party, even against the line adopted by the Catholic Bishops' Conference.